Raman study of silicon telluride nanoplates and their degradation. (25th June 2022) - Hathaway, Evan; Chen, Jiyang; Gonzalez-Rodriguez, Roberto; Lin, Yuankun; Cui, Jingbiao
Abstract: Silicon telluride (Si2 Te3 ) has emerged as one of the many contenders for 2D materials ideal for the fabrication of atomically thin devices. Despite the progress which has been made in the electric and optical properties of silicon telluride, much work is still needed to better understand this material. We report here on the Raman study of Si2 Te3 degradation under both annealing and in situ heating with a laser. Both processes caused pristine Si2 Te3 to degrade into tellurium and silicon oxide in air in the absence of a protective coating. A previously unreported Raman peak at ∼140 cm −1 was observed from the degraded samples and is found to be associated with pure tellurium. This peak was previously unresolved with the peak at 144 cm −1 for pristine Si2 Te3 in the literature and has been erroneously assigned as a signature Raman peak of pure Si2 Te3, which has caused incorrect interpretations of experimental data. Our study has led to a fundamental understanding of the Raman peaks in Si2 Te3, and helps resolve the inconsistent issues in the literature. This study is not only important for fundamental understanding but also vital for material characterization and applications.